IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII-A SMP NEGERI 2 SAMBUNGMACAN SRAGEN - Indarto, Slamet; Agung S., Leo; S., Sariyatun (Sebelas Maret University (UNS), 2015)
The purpose of this research is to know which with the implementation of cooperative Jigsaw learning model can increase motivation and student learning outcomes on Social Science in VII-A Class, SMP Negeri 2 SambungmacanSragen. This research used Classroom Action Research (PTK) procedure. This subject of this research was VII-A Class, SMP Negeri 2 Sambungmacan Sragen with 32 students. This research consist of three cycles and each cycle in this research held in one meeting. The stages in this research are planning, implementation, observation and reflection. The methods of collecting observation data used observation, documentation, note field, and test. The technique of data analysis that used is qualitative data analysis technique. The result can be conclude: the implementation of Jigsaw learning model through image medium on basic competence describing the activity of economic principle can increase excitement or enthusiasm of student learning and lots of fun. The implementation of Jigsaw learning model through image medium can increase motivation and student learning outcomes quite high. Based on the questionnaire answer of Social Science learning motivation that given to student in the first cycle, can be known that the average is 128.13 or 64.06%, the second cycle is 134.53 or 67.27%, and the third cycle is 152.50 or 76.25%. While the value of cognitive post-test learning outcomes average in first cycle is 67.66 with completeness achievement 59.38, the second cycle is 76.09 with completeness achievement 78.13, and the third cycle is 85.00 with completeness achievement 100%, accordingly can be conclude thatthe implementation of Jigsaw learning model through image medium at Social Science learning can increase the motivation and student learning outcomes in VII-A Class, SMP NegeriSambungmacanSragen.